دور الابتكار التسويقي في تحقيق استدامة الميزة التنافسية للشركات - بن علي, عبد الرزاق (جامعة الوادي - University of Eloued, 2014)
تركز هذه الدراسة على عرض الابتكار التسويقي باعتباره آخر أنواع الابتكارات التي يمكن أن تؤدي إلى استدامة الميزة التنافسية، لا سيما عندما تكون جنبا إلى جنب مع ابتكار المنتج، كما عرضت هذه الورقة ديناميكيات الابتكار التسويقي في جميع مرإحل دورة حياة الصناعة، كذلك درست، الآثار المترتبة عن الابتكار التسويقي على استدامة الميزة التنافسية وأداء الشركة، ثم بينت الدراسة أن التعاون الإيجابي الذي ينشأ بين الابتكار التسويقي وابتكار المنتجات يؤدي إلى ميزة تنافسية أكبر، وبالتالي فإن نجإح الشركة يكون من أي منهما منفردا . أخيرا، لفتت الدراسة إلى أن الابتكار للاستدامة ذو مزيج متعدد الأبعاد باعتباره عنصرا رئيسيا جديدا لميزة تنافسية مستدامة في بيئة اليوم سريعة التغير. This study focuses on the presentation of marketing innovation as the latest type of innovation that can sustain competitive advantage, especially when it comes to product innovation. This paper presents the dynamics of marketing innovation in all aspects of the life cycle of the industry, The study showed that positive cooperation between marketing innovation and product innovation leads to a greater competitive advantage, and therefore the company is not one of them. Finally, the study found that innovation for sustainability has a multidimensional mix as a key element of a sustainable competitive advantage in today's rapidly changing environment.
مقال
Keywords: الابتكار, الابتكار التسويقي, ابتكار المنتج, الاستدامة، الميزة التنافسية, دورة حياة الصناعة; Innovation, marketing innovation, product innovation, sustainability, competitive advantage, industry lifecycle.